Cardiovascular autonomic dysfunction after stroke - Jimenez-Ruiz, Amado; Racosta, Juan M.; Kimpinski, Kurt; Hilz, Max-Josef; Sposato, Luciano A. (Neurological Sciences, 2021)
Strokes are the paradigmatic example of the sudden impairment of the cerebral regulation of cardiac autonomic regulation. Although several aspects of dysautonomic cardiovascular regulation post stroke remain unanswered, there has been a wealth of research in this area in the last decade. In this article, we present a state-of-the-art review on the anatomical and functional organization of cardiovascular autonomic regulation, and the pathophysiology, incidence, time course, diagnosis, clinical aspects, prognosis, and management of post-stroke cardiovascular autonomic dysfunction.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Atrial fibrillation; Autonomic dysfunction; Cardiovascular complications; Heart failure; Parasympathetic; Stroke; Sympathetic